Evaluation of Apical Leakage in Root Canals Obturated with Three Different Sealers in Presence or Absence of Smear Layer - Mokhtari, Hadi; Shahi, Shahriar; Janani, Maryam; Frough Reyhani, Mohammad; Mokhtari Zonouzi, Hamid Reza; Rahimi, Saeed; Sadr kheradmand, Hamid Reza (Iranian Endodontic Journal, 2015)
Introduction: Microleakage can result in failure of endodontic treatment. An important characteristic of endodontic sealer is sealing ability. The aim of this experimental study was to compare the apical leakage of teeth obturated with gutta-percha and three different sealers (resin- and zinc oxide eugenol-based) with/without smear layer (SL). Materials and Methods: In this study, 100 single-rooted teeth were used after cutting off their crowns. Cleaning and shaping was carried out with step-back technique and the samples were randomly divided into three groups (n=30) which were then divided into two subgroups (n=15) according to the presence/absence of SL. Two negative and positive control groups (n=5) were also prepared. In the various groups, the canals were obturated with gutta-percha and either of the test sealers (AH-26, Adseal or Endofill). The samples were submerged in India ink for 72 h. Then they were longitudinally sectioned and observed under a stereomicroscope at 20× magnification. Data were analyzed with descriptive statistical methods and one-way ANOVA. The significance level was set at 0.05. Results: The mean penetration length of dye in AH-26, Adseal and Endofill samples were 2.53, 2.76 and 3.03 mm, respectively. The differences between three groups were not significant (P>0.05); also, the mean dye penetration in AH-26, Adseal and Endofill samples in presence or absence of the SL was not significantly different. Conclusion: AH-26, Adseal and Endofill were similarly effective in prevention of apical microleakage. Differences in the mean dye penetration between the groups with/without the SL were not statistically significant.